2018
DOI: 10.1017/jrc.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Exploring Family Life in Men Following Neurosurgery for Adult Onset Epileptic Seizures

Abstract: This study explored family relationship dynamics of men with Adult Onset Epileptic Seizures (AOES) following an elective lobectomy procedure to address their frequent seizure activity. Informants were five Australian men with history of adult-onset epilepsy for which they received neurosurgery (aged 34–59 years). Thematic analysis following semi-structured interviews yielded three themes: role marginalization, role dependency and role enmeshment. All the men reported significant role marginalization in not bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…35(p.206) However, the impact of epilepsy on parenting in male participants was only clearly described in one study. 38 This study reported three types of changes in participants' perception of their role within the familyrole marginalization, role dependency and role enmeshment.…”
Section: Theme 3: Impact Of Stigma On Everyday Life and Associated Re...mentioning
confidence: 95%
See 2 more Smart Citations
“…35(p.206) However, the impact of epilepsy on parenting in male participants was only clearly described in one study. 38 This study reported three types of changes in participants' perception of their role within the familyrole marginalization, role dependency and role enmeshment.…”
Section: Theme 3: Impact Of Stigma On Everyday Life and Associated Re...mentioning
confidence: 95%
“…All were included, as they focused on different research questions and thus provided complementary information (n = 8). [35][36][37][38][39][40][41][42] <Insert Figure 1…”
Section: Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation